Political Stability, Corruption, and Economic Development : Evidence frim WAMZ Countries - SuleYa'u Hayewa; Adijat Olubukola Olateju (MultiTech Publisher, 2024)
The paper has analyzed the political stability, corruption and economic development in the West African Monetary Zone (WAMZ) countries for the period of 2000 to 2020. The common properties of the panel data were first checked to avoid mis-specification bias and hence biased statistical results. Firstly, the CD test revealed no evidence/absence of cross sectional dependence among the countries which validates the use of traditional panel unit root that does not take account of cross-sectional dependence. The results of panel unit root test proposed by Levin et al (2002) revealed that the variables are integrated of order zero i.e. I (0). Based on this, the paper explores within the panel VAR framework. Evidence from impulse response functions revealed that, political stability and rule of low are economic development promoters while corruption hampers economic development in the region. The results from variance decomposition indicate that the variables under study contribute or hinder economic development in the WAMZ countries. Based on the results the paper recommends that, transparency and accountability at all level of government affairs as well as respecting the constitution in these nations should be preserved in order to overcome all social and political injustice among the countries under study.